Correction of unaesthetic Gummy Smile - Singh, Guljot; Ajmera, Pragya; Singh, Jagir; Agarwal, Khushboo; Kumar, Narender; Chikhalikar, Shravani (Journal of Neonatal Surgery, 2025)
Introduction Excessive gingival display commonly refers to “gummy smile” is an aesthetic concern for patient. It is a multifactorial condition in which an overexposure of the maxillary gingiva (>3mm) is present during smiling. Lip repositioning is a simple surgical procedure to treat ‘gummy smile’. Objective;The report aimed lip repositioning technique to decrease the amount of excessive gingival display in patients with gummy smile. Methodology: Under LA, an incision is given in the depth of vestibule, borders are marked, a partial thickness flap is raised from left maxillary first molar to the right maxillary first molar at the mucogingival junction. Two incisions were joined and strip of partial thickness flap has been removed exposing the underlying connective tissue. These two incisions were closed using interrupted suture. ResultsThe repositioning of the lip is more coronal position narrowing the vestibular depth with restricted muscle pull, with competent lips. The excessive gingival display was decreased to 2mm without relapse. Conclusion; Lip repositioning procedure is an effective way of reducing the EGD. However, long-term stability of the results needs to be seen. None the less, this procedure appears to be a promising alternative treatment option for excessive gingival display.